Primary Orbital Melanoma: Presentation, Treatment, and Long-term Outcomes for 13 Patients - Rose, Anna M.; Luthert, Philip J.; Jayasena, Channa N.; Verity, David H.; Rose, Geoffrey E. (Frontiers in Oncology, 2017)
BACKGROUND: Periocular melanoma is a rare but often deadly malignancy that arises in the uvea (commonest origin), conjunctiva or orbit (rarest primary site). Melanoma accounts for 5-10% of metastatic/secondary orbital malignancies, but only a tiny proportion of primary orbital neoplasia. Primary orbital melanoma (POM) is exceedingly rare, with approximately 50 cases reported to date. METHODS: All patients seen in the orbital unit at a tertiary referral hospital (1991-2016) with a biopsy-proven diagnosis of POM were identified from a diagnostic database and were studied. The case notes, imaging, surgical approach and histology were reviewed. RESULTS: Thirteen patients (5 male; 38%) presented with isolated malignant melanoma of the orbit, for which no other primary site was identified at presentation or during an average follow-up of 44 months (median 22; range 0 – 13 years). The patients presented between the ages of 40 and 84 years (mean 55.5; median 48 years) and typically gave a short history of rapidly increasing proptosis and eyelid swelling. On the basis of history, a malignant lesion was suspected in most patients and all underwent incisional biopsy, with debulking of the mass in 10 (77%) patients, and skin-sparing exenteration in 3/13 (23%). Ten patients underwent orbital radiotherapy and the survival to date ranged from 9 months to 14 years (mean 55 months; median 23 months); two patients received solely palliative care for widespread disease and one patient refused orbital radiotherapy. Five of the 13 (38%) patients died from the disease. DISCUSSION: Primary orbital melanoma is a very rare malignancy, but clinical analysis of this cohort gives insight into disease presentation and prognosis. The tumour typically presents with a rapidly-progressive, well-defined mass that is, in some cases, amenable to macroscopically-intact excision. Unusual for malignant melanoma, some of these patients can show an unusually long period of quiescent disease after surgical debulking and radiotherapy.